Research Progress on Casing Deformation Mechanisms of Horizontal Wells in Coalbed Methane Reservoirs - Zhang, Yutong; Li , Mingfei (Scientific Journal of Technology, 2026)
With the advancement of coalbed methane exploration and development into deep formations and structurally complex areas, horizontal well technology has become a key means for the development of deep CBM. However, casing deformation problems occur frequently throughout its full life cycle, severely restricting the efficient development of horizontal wells. Based on existing literature, this paper systematically combs the core mechanisms of casing deformation in CBM horizontal wells from two major dimensions: geological factors and engineering factors. In terms of geological factors, the anisotropy of in-situ stress field and reservoir heterogeneity, the special mechanical properties of coal rocks with granulated and cataclastic structures, and the migration of overlying strata and mining-induced stress disturbance are the root causes. Among engineering factors, drilling and completion processes and well trajectory design, as well as defects in cementing quality and cement sheath performance, are important auxiliary causes. Meanwhile, this paper summarizes the controversial points in current research regarding core inducing factors and quantitative numerical simulation. Finally, it is pointed out that future research needs to deepen the study on the coupling mechanism of geological-engineering factors and promote the integration of mechanism research with engineering practice, so as to provide a theoretical basis for the optimization of casing deformation prevention and control technologies.